Engineering global e-commerce sites a guide to data capture, content, and transactions - Bean, James (James D.) (San Francisco, Calif. : Morgan Kaufmann ; Oxford : Elsevier Science, 2003)
"This book is a boon to technology professionals who are responsible for global integration projects. Faced with the mind-boggling complexities of standardizing global data, global processes and global e-commerce, even the most experienced professionals are often at a loss. James Bean has created an extraordinary compilation of standards information, and provided his insight on how to resolve complex integration problems. This book will benefit IT community at large, and I would encourage both specialists and novices alike to bring this book into their personal libraries."--Arka Mukherjee, Ph. D., CEO, Global IDs Inc. A practitioner's guide to developing global e-commerce sites, focusing on the design and engineering of Web forms for global data collection and alignment with widely recognized international standards, XML structures, and XML vocabularies. The author describes the globalization problem, identifies common design errors, provides a representative scenario, and introduces effective solutions and techniques. Structured around a practical, "real-world" theme, this book is written for the hands-on practicioner in any mid- to large-sized company engaging in international ecommerce (B2C, B2B, etc.) * Presents effective techniques for flexible and extensible data capture * Provides techniques for using the most recognized international data standards and describes the synergies, value and importance of XML as a transaction definition medium * Only book on the subject written from a software engineering point of view.
Global e-commerce and the Web -- Defining the terms global, regional, international, and local -- Global standards -- Globalized data and transactions -- Globalization process and techniques -- Transaction engineering -- Enterprise application integration -- The complexities of mobile e-commerce.
Includes bibliographical references (p. 205-209) and index.
Keywords: Electronic commerce; Web sites -- Design; XML (Document markup language); Electronic books